Hukum Menggadaikan Harta Pinjaman Menurut Hukum Islam - Angga lestari Nugraha (Journal of Islamic Economic Studies, 2025)
Pawning is pledging property as collateral for the debt borrowed. However, if the status of the mortgaged property is the result of borrowing, of course there are views regarding the legal status of pawning borrowed assets. The purpose of this research is to find out about the legal status of pawning borrowed assets according to Islamic law. The research method is a qualitative method which aims to understand in depth the law of pawning borrowed assets according to Islamic law. The data in this research are in the form of documents, books and journals related to this research. This research also uses data collection techniques using the literature study method (library research). The results of this research can be concluded that pawning loaned assets is permitted on condition that the owner of the property gives permission. In Islam, loaned assets are only used as collateral, there is no transfer of ownership, so that the loan proceeds can also be used as collateral in pawning. This research is expected to increase insight into Islamic treasures, especially in the field of sharia economics.